2017
DOI: 10.1016/j.eneco.2017.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Good volatility, bad volatility: What drives the asymmetric connectedness of Australian electricity markets?

Abstract: Efficient delivery of network services and the electricity infrastructure to meet the long-term consumer's interests are the main objectives and the strategies of a national electricity market, while the main interests of generators are to maximize their profit through pricing strategies. Therefore, the objective of this study is to explore whether electricity prices across the four Australian States display symmetric price volatility connectedness. The study is the first attempt in the literature to make use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 53 publications
5
44
0
Order By: Relevance
“…In addition to returns connectedness, we investigate asymmetry in the connectedness of cryptocurrency markets. In the broad empirical findings, asset markets usually present asymmetry effects in response to good news and bad news (e.g., Apergis et al, 2017;Barunik et al, 2016). However, there is thus far no clear evidence in the cryptocurrency market to confirm this rule.…”
Section: Various Connectedness Network Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to returns connectedness, we investigate asymmetry in the connectedness of cryptocurrency markets. In the broad empirical findings, asset markets usually present asymmetry effects in response to good news and bad news (e.g., Apergis et al, 2017;Barunik et al, 2016). However, there is thus far no clear evidence in the cryptocurrency market to confirm this rule.…”
Section: Various Connectedness Network Measuresmentioning
confidence: 99%
“…Investors and risk managers can also benefit from building network of connectedness across asset classes to adjust their investment and hedging decisions. Prior studies have uncovered the network of connectedness among and within different assets/markets that include equities (Fowowe and Shuaibu, 2016;Shahzad et al, 2018;, bonds (Louzis, 2015;Ahmad et al, 2018), currencies (Baruní k, et al, 2017;Singh et al, 2018), commodities (Ji et al, 2018a & b;Zhang and Broadstock, 2018), and interest rates (Louzis, 2015). Generally, empirical evidence suggests that connectedness in both return and volatility is significant, time-varying, and is shaped by crisis periods (Shahzad et al, 2018;Zhang and Broadstock, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of previous studies on electricity volatility spillovers make use of low frequency data (daily or aggregated daily prices) and employ MGARCH models. However, due to the increasing availability of intraday data, recent studies have constructed realized volatility non-parametrically from intraday returns and employed the Yilmaz (2009, 2012) spillover index within a VAR framework (e.g., Han et al 2017;Apergis et al, 2017a). Han et al (2017) found that spillover effects are more pronounced in the physically interconnected regions, exhibiting time and event dependent patterns.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Han et al (2017) found that spillover effects are more pronounced in the physically interconnected regions, exhibiting time and event dependent patterns. Apergis et al (2017a) applied VAR to quantify asymmetries in volatility spillover emerging from good and bad volatility and showed that Australian regional electricity markets are linked asymmetrically.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation